Do capital buffers mitigate volatility of bank lending? A simulation study - Frank Heid; Ulrich Krüger (Deutsche Bundesbank, 2011)
Critics claim that capital requirements can exacerbate credit cycles by restricting lending in an economic downturn. The introduction of Basel 2, in particular, has led to concerns that risksensitive capital charges are highly correlated with the business cycle. The Basel Committee is contemplating a revision of the Basel Accord by introducing counter-cyclical capital buffers. Others claim that capital buffers are already large enough to absorb fluctuations in credit risk. We address the question of the pro-cyclical effects of capital requirements in a general framework which takes into account banks' potential adjustment strategies. We develop a dynamic model of bank lending behavior and simulate different regulatory frameworks and macroeconomic scenarios. In particular, we address two related questions in our simulation study: How do business fluctuations affect capital requirements and bank lending? To what extent does the capital buffer absorb fluctuations in the level of mimimum required capital?
Keywords: C61; E32; E44; G21; 330; Minimum capital requirements; regulatory capital; capital buffer; cyclical lending; pro-cyclicality